Cardiovascular risk factors in relation to hair polycyclic aromatic hydrocarbons in the NESCAV study - Feng-Jiao Peng; Chia-An Lin; Rin Wada; Barbara Bodinier; Alba Iglesias-González; Paul Palazzi; Sylvie Streel; Michèle Guillaume; Marc Chadeau-Hyam; Brice M.R. Appenzeller (Environment International)
Previous studies have found associations between exposure to polycyclic aromatic hydrocarbons (PAHs) and cardiovascular risk factors. However, the internal dose of PAH exposure was often examined by quantifying monohydroxylated metabolites of PAHs (OH-PAHs) in urine, which can only reflect recent exposure. On the other hand, hair covers wider temporal windows than urine and has been demonstrated to be a suitable matrix for PAH exposure assessment. Using hair analysis, here we investigated the associations between PAH exposure and obesity, diabetes, hypertension, dyslipidemia, and metabolic syndrome (MetS) and its components in a cross-sectional study of adults aged 18–69 years and enrolled in the Nutrition, Environment and Cardiovascular Health (NESCAV) survey conducted in 2007–2009 in Luxembourg. In addition, we also examined hair cotinine and nicotine because they are well-established biomarkers of tobacco smoke exposure. Associations were explored separately for men (n = 265) and women (n = 347) by logistic regression with adjustment for potential confounders. We found positive associations of OH-PAHs with diabetes in both men and women, positive and inverse associations with obesity and positive associations with hypertension/elevated blood pressure and dyslipidemia/elevated triglycerides (TG) in men, and inverse associations with hypertension but positive associations with MetS, elevated waist circumference and reduced high-density lipoprotein cholesterol (HDL-C) in women. These results may suggest that men and women differ in cardiometabolic responses to environmental PAH exposure. As regards hair cotinine and nicotine, they were associated with diabetes/elevated fasting plasma glucose, elevated blood pressure, and dyslipidemia/elevated TG/reduced HDL-C in men and women. Our results suggest that exposure to PAHs and tobacco smoke may be associated with cardiometabolic health risk. Future prospective studies are warranted to corroborate these findings.